PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MULTIDISPLINER (Dialektika Konsep Pendidikan Berbasis Agama dan Budaya) - Septyana Tentiasih; Maftuhah; Suharsono (Jurnal Pendidikan Islam, 2024)
The purpose of this study is to examine multidisciplinary Islamic education in thedialecta of the concept of religion and culture-based education from the first side, theimportance of multidisciplinary learning in the context of Islamic education and thesecond, through this approach can help students understand religion and cultureholistically. The research method used in this research is a type of qualitative researchusing a library research approach. The results of the research are that multidisciplinaryIslamic Education learning is an approach that combines several disciplines in onescientific family to study the problems that exist in Islamic education. The purpose ofthis multidisciplinary approach is to add studies so that what is studied is more accurateby using various points of view. The relationship between religion and culture is verystrong. A teacher must emphasize that culture has an important role in human life andexplain which cultures are good and which are bad that must be adopted in the processof learning Islam.